PSYCHOSOMATIC CONSEQUENCES OF TEACHERS' OCUPPATIONAL STRESS - Anna Romanowska-Tolloczko (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The need to adapt to the ever-increasing socio-professional requirements carries many risks to human health, both in somatic and psychological aspects. Strong stress associated with work leads to the occurrence of burnout syndrome. Persons performing so called aid professions, where teachers belong to a special group, are usually vulnerable to this syndrome. The aim of this paper is to present the causes, course and consequences of teacher burnout and to highlight the multidimensional nature of the phenomenon, indicating possible corrective and preventive actions. Among the that contribute to burnout important are environmental , organizational and subjective factors. Subjective factors like professional training and personality dispositions, are treated as the primary determinants of resistance or susceptibility of individuals to stress. They can intensify or protect against burning out. The lack of ability to counter stress is considered crucial in the formation and accumulation of burnout symptoms.